Anger as a Basic Emotion and Its Role in Personality Building and Pathological Growth: The Neuroscientific, Developmental and Clinical Perspectives - Williams, Riccardo (Frontiers in Psychology, 2017)
Anger is probably one of the mostly debated basic emotions, owing to difficulties in detecting its appearance during development, its functional and affective meaning (is it a positive or a negative emotion?), especially in human beings. Behaviors accompanied by anger and rage serve many different purposes and the nuances of aggressive behaviors are often defined by the symbolic and cultural framework and social contexts. Nonetheless, recent advances in neuroscientific and developmental research, as well as clinical psychodynamic investigation, afford a new view on the role of anger in informing and guiding many aspects of human conducts. Developmental studies have confirmed the psychophysiological, cognitive and social acquisition that hesitate in the pre-determined sequence appearance of anger and rage in the first two years of life. The so-called affective neurosciences have shown the phylogenetic origin of the two circuits underlying the emergence of anger along with its evolutionary role for promoting survival. This view has been integrated by the psychodynamic theory of motivational systems that attribute a double role to anger: on the one hand, this affect works as an inwardly directed signal concerning a pressure to overcome an obstacle or an aversive situation; on the other hand, anger is also an outwardly directed communicative signal establishing differentiation and conflict within interpersonal relationships and affective bonds. Of course, human peculiar mental functioning requires the appraisal of such signals by higher cortical functions and, there is little doubt that the meaning that orientates individual behaviors is, eventually, construed on a social and cultural level. At the same time, everyday life experiences as well as clinical insights into psychopathic, narcissistic and borderline personality pathology clearly illustrate the necessity to correctly interpret and give answers to the basic questions raised around the topic of anger as a basic emotion.